(untitled) (European Journal of Economics, Finance and Business Development, 2025)
The article studies the important features of financing in small businesses. Information on the demography of enterprises and organizations of the Republic of Uzbekistan, information on enterprises and organizations with foreign investment as of May 12, 2025, information on enterprises and organizations with foreign investment as of May 12, 2025, is analyzed. Also, the relationship between entrepreneurship and innovative investment activities is studied.